Manajemen Pembelajaran Berbasis Problem Based Learning Di Sekolah Dasar Negeri di Kota Medan - Srie Faizah Lisnasari; Ulfa Sri Rezeki (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
The research aims to determine the effectiveness of problem-based learning (PBL)-based learning management at public elementary schools in Medan City. This research was conducted in December 2022. The population in this study were all first grade students of public elementary schools in Medan City, with a sample of 24 elementary schools. Sampling was carried out using the Puposive Sampling technique. This study uses a descriptive quantitative research method. The research shows the following results: 50% of the cognitive aspects have a very high category, the results of the affective aspect which consist of: the ability to behave honestly and discipline students 50% are in the very good category, on the ability to be caring, polite and confident, which gets the category very good attitude as much as 50%. Furthermore, on the ability of students to be responsible and communicative, as much as 58% is in the very good category. In the psychomotor abilities of students, the results of the ability to present orally the parts of the student's body were obtained, very good as much as 46%, good value as much as 54%. In the skills of presenting rules for maintaining body health, students who got very good as much as 58% and on students' skills in demonstrating limb movements through musical accompaniment, were in the very good category as much as 42% and in the good category 58%. The conclusions of the research show that learning management based on problem-based learning is effective on the abilities of first grade students of public elementary schools in Medan city